2008
DOI: 10.1002/hep.22311
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and steatosis influence serum and hepatic inflammatory markers in chronic hepatitis C

Abstract: Obesity and fatty liver are commonly observed among patients with chronic hepatitis C virus (HCV) and are risk factors for increased hepatic fibrosis. Obesity is accompanied by a low-grade, chronic inflammatory response that may contribute to pathogenesis of obesityrelated comorbidities. To assess whether obesity and steatosis potentiate expression of inflammatory markers in chronic HCV, serum protein and hepatic messenger RNA (mRNA) levels of c-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 38 publications
(39 reference statements)
4
51
0
3
Order By: Relevance
“…Petit et al (137) found a correlation between serum adiponectin concentration and hepatic steatosis, but in the study by Jonsson et al (139), such a relationship was found only in men with CHC. In the study by Durente-Mangoni et al (140), hypoadioponectinemia in CHC was associated with the grade of hepatic steatosis, and a changed balance between adiponectin and TNFα was suggested.…”
Section: Adiponectin In Chronic Hepatitismentioning
confidence: 92%
See 2 more Smart Citations
“…Petit et al (137) found a correlation between serum adiponectin concentration and hepatic steatosis, but in the study by Jonsson et al (139), such a relationship was found only in men with CHC. In the study by Durente-Mangoni et al (140), hypoadioponectinemia in CHC was associated with the grade of hepatic steatosis, and a changed balance between adiponectin and TNFα was suggested.…”
Section: Adiponectin In Chronic Hepatitismentioning
confidence: 92%
“…TNFα is a proinflammatory cytokine/adipokine that is elevated and positively associated with the inflammatory activity grade and fibrosis stage in CHC (47,48). Visfatin increases TNFα production in human peripheral blood mononuclear cells and in murine liver hepatocytes (25).…”
Section: Visfatin and Necro-inflammatory Activity In Chronic Hepatitismentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of IR in CHC with steatosis has been reported to be due to the HCV infection and NAS independently or together [14]. Increased levels of proinfl ammatory cytokines interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) in patients with CHC and visceral obesity also contribute to development of liver steatosis and IR [15]. A metaanalysis has shown that CHC patients have about 1.7-fold increased risk of development type 2 DM compared with noninfected controls [16].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown various cytokines, which are crucial indicators of inflammation, such as TGF-β1 and TNF-α, are very important activators during the process of liver fibrosis. [253][254][255] TNF-α has been reported closely related to liver fibrosis and cirrhosis. 255 We investigated the level of TNF-α after we treated HSCs with TGF-β1 shRNA.…”
Section: Discussionmentioning
confidence: 99%